PERBAIKAN KEMASAN UNTUK MENINGKATKAN NILAI JUAL SOSIS SOLO DI UKM SOSIS GAJAHAN [PACKAGING IMPROVEMENT TO INCREASE SELLING VALUE OF SOSIS SOLO IN SMALL AND MEDIUM ENTERPRISE (SME) SOSIS GAJAHAN] - Asri Nursiwi; Dwi Ishartani; Siswanti Siswanti; Ardhea Mustika Sari (Jurnal Sinergitas PKM & CSR, 2019)
Sosis solo is a traditional food from Solo which is made from an omelette with meat filling. Sosis solo usually served as snacks in various events. In Solo there are many Small and medium enterprise (SME) producing sosis solo, one of them is SME Sosis Gajahan.  The SME has been developing and know the opportunity that sosis solo as a typical food from Solo, has the potential to be developed as typical Solo gift. However, there are problems faced by these SME, namely 1) the packaging is not attractive and has not been labeled in accordance with the requirements of the food industry and 2) the shelf life of sosis solo is short, less than 24 hours. The aims of the community service activity were to improve the packaging of the sosis solo so that increasing the seelling value. To overcome these problems, had been did 1) improvement of packaging and labeling, and 2) introduction of vacuum packaging to package the sosis solo so that the shelf life is longer. The results obtained from the activity are the better new packaging designs for sosis solo and more attractive so that it increasing the selling value of sosis solo. Sosis solo packaged with a vacuum method followed by cold storage has longer shelf life. It has an impact on wider marketing reach.